2008
DOI: 10.1021/ac8014356
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Energy Transfer-Amplifying Fluorescence Quenching at the Surface of Silica Nanoparticles toward Ultrasensitive Detection of TNT

Abstract: This paper reports a resonance energy transfer-amplifying fluorescence quenching at the surface of silica nanoparticles for the ultrasensitive detection of 2,4,6-trinitrotoluene (TNT) in solution and vapor environments. Fluorescence dye and organic amine were covalently modified onto the surface of silica nanoparticles to form a hybrid monolayer of dye fluorophores and amine ligands. The fluorescent silica particles can specifically bind TNT species by the charge-transfer complexing interaction between electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
195
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(201 citation statements)
references
References 40 publications
6
195
0
Order By: Relevance
“…In comparison with the other work on MIP@QDs for use in detection applications, [25][26][27][28]41,42 the developed DMIP@QDs showed excellent selectivity but low sensitivity. This problem of low sensitivity commonly exists for MIP@QDs-based systems.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In comparison with the other work on MIP@QDs for use in detection applications, [25][26][27][28]41,42 the developed DMIP@QDs showed excellent selectivity but low sensitivity. This problem of low sensitivity commonly exists for MIP@QDs-based systems.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…27 Gao et al reported a resonance energy-transfer-amplifying fluorescence quenching at the surface of silica nanoparticles for the ultrasensitive detection of TNT. 28 Stringer et al prepared a fluorescent QDs-labeled imprinted polymer for the detection of nitroaromatic explosives in solution. 30 Instead of preparing the QDs beforehand and incorporating them into the imprinted polymers, QDs were added as a postprocessing step.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When the excited-state electrons of the donor return to ground state through the pathway of a, b, and c, the ground-state electrons of the PC will transit to the excited states through the corresponding pathway of a′, b′, and c′, respectively, due to the polar-polar resonance of donor and acceptor. The coupled transitions will lead to the highly efficient quenching of donor fluorescence (Gao et al, 2008). On the other hand, it has to be noted that the fluorescence of donor may also be quenched by the charge transfer, as illustrated in Fig.…”
Section: Preparation and Detection Principle Of Sio 2 @Nbd@mipsmentioning
confidence: 99%
“…This calls in for some improvement in the sensing techniques, attracting considerable research efforts in recent years. Among the various techniques, fluorescence-based sensors appear simple, cost-effective, and highly sensitive detection modalities [13][14][15][16][17]. Adding to the list, miniaturized smart sensors based on one-dimensional (1D) nanostructures have gained much attention owing to their fast and high sensitivity towards enhanced adsorption.…”
Section: Introductionmentioning
confidence: 99%